(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
The moment I decided to become a teacher is very clear. I was taking a graduate International Relations course at the London School of Economics entitled “Gender, Justice, and War.” The students in the department were intelligent, progressive, and well-read individuals from around the world. One morning we were asked the question, “what can we do with a rogue state if we don’t want to use either sanctions or war?” No one had an answer. No one had ideas. There was thoughtful, but lasting, silence. In that moment I realized that war is indeed inevitable… not because of ‘man’s inherent nature’ or the state system that we’d been reading about, but because of a simple lack of creativity. I wondered how violence can be prevented if it is- literally- the only thing that we can think to do? I decided then that an important part of overcoming war must come from a deliberately innovative education. As teachers, we can bring peace content and a way of thinking that can foster and further creativity, and hence, peace.